How many implants are needed for mandibular full-arch rehabilitation? - Giovanetti, Karina (2020)
Aim: To analyze the stress distribution at the peri-implant bone tissue of mandible in full-arch implant-supported rehabilitation using a different number of implants as support. Methods: Three-dimensional finite element models of full-arch prosthesis with 3, 4 and 5 implants and those respective mandibular bone, screws and structure were built. ANSYS Workbench software was used to analyze the maximum and minimum principal stresses (quantitative analysis) and modified von Mises stress (qualitative analysis) in peri-implant bone tissue after vertical and oblique forces (100N) applied to the structure at the cantilever site (region of the first molars). Results: The peak of tensile stress values were at the bone tissue around to the distal implant in all models. The model with 3 implants presented the maximum principal stress, in the surrounding bone tissue, higher (~14%) than the other models. The difference of maximum principal stress for model with 4 and 5 implants was not relevant (~1%). The first medial implant of the model with 5 implants presented the lower (17%) stress values in bone than model with 3 implants. It was also not different from model with 4 implants. Conclusion: Three regular implants might present a slight higher chance of failure than rehabilitations with four or five implants. The use of four implants showed to be an adequate alternative to the use of classical five implants.